2001
DOI: 10.1016/s1074-5521(01)00075-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction of a vancomycin derivative with bacterial enzymes involved in cell wall biosynthesis

Abstract: Hydrophobic vancomycins interact directly with a select subset of bacterial membrane proteins, suggesting the existence of discrete protein targets. Transglycosylase inhibition may play a role in the enhanced bioactivity of semisynthetic glycopeptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…There was, notably, a significant difference in the sensitivities of telavancin and vancomycin to antagonism by dKAA in this assay. The IC 50 for vancomycin shifted greater than 10-fold in the presence of 0.5 mM dKAA, while the highest concentration of dKAA tested (40 mM) was required to increase the IC 50 for telavancin 10-fold ( Table 1). The antibacterial activity of telavancin, as measured by MIC determination, was more potent than that of vancomycin.…”
Section: Inhibition Of Macromolecular Biosynthesis In Intact Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was, notably, a significant difference in the sensitivities of telavancin and vancomycin to antagonism by dKAA in this assay. The IC 50 for vancomycin shifted greater than 10-fold in the presence of 0.5 mM dKAA, while the highest concentration of dKAA tested (40 mM) was required to increase the IC 50 for telavancin 10-fold ( Table 1). The antibacterial activity of telavancin, as measured by MIC determination, was more potent than that of vancomycin.…”
Section: Inhibition Of Macromolecular Biosynthesis In Intact Cellsmentioning
confidence: 99%
“…One proposed mechanism is that hydrophobic substituents of lipoglycopeptides confer strong dimerization and membrane-anchoring properties that allow for increased binding affinities for peptidoglycan intermediates at the target site in bacteria (1,3,4,9). The second proposed mechanism is that the liposaccharide elements of lipoglycopeptides interact directly with and inhibit transglycosylase enzymes that mediate the polymerization of precursors into immature, un-cross-linked peptidoglycan (16,23,24,30,50).…”
mentioning
confidence: 99%
“…These analogues were shown to inhibit the transglycosylation step of peptidoglycan biosynthesis, and we thus suggested that 2 and 5 interact directly with a component of the transglycosylation complex. Sinha Roy et al (8) provided support for this hypothesis recently when they showed that penicillin-binding protein 1b (PBP1b), the major transglycosylase in Escherichia coli, is retained on an affinity column derivatized with 2 or fragments thereof. We now report a study showing that 2 and 5 inhibit PBP1b by interacting directly with the enzyme (Fig.…”
mentioning
confidence: 98%
“…These observations suggest that the hydrophobic vancomycin derivatives inhibit transglycosylation independently of substrate binding, but probably by a mechanism in which they directly interact with the enzyme. It was possible to utilize this interaction in order to isolate PBPs from a crude mixture of E. coli membrane proteins by affinity chromatography, hydrophobic vancomycin derivatives being immobilized on solid support [85]. A second advantage of the semisynthetic hydrophobic glycopeptide derivatives, besides their activity against VRE, is their cellular response.…”
Section: Peptidoglycanmentioning
confidence: 99%